2016
DOI: 10.1021/acsami.5b11786
|View full text |Cite
|
Sign up to set email alerts
|

Porous Core–Shell Fe3C Embedded N-doped Carbon Nanofibers as an Effective Electrocatalysts for Oxygen Reduction Reaction

Abstract: The development of nonprecious-metal-based electrocatalysts with high oxygen reduction reaction (ORR) activity, low cost, and good durability in both alkaline and acidic media is very important for application of full cells. Herein, we developed a facile and economical strategy to obtain porous core-shell Fe3C embedded nitrogen-doped carbon nanofibers (Fe3C@NCNF-X, where X denotes pyrolysis temperature) by electrospinning of polyvinylidene fluoride (PVDF) and FeCl3 mixture, chemical vapor phase polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(105 citation statements)
references
References 36 publications
4
100
0
Order By: Relevance
“…It is already reported that the excessive pyridinic nitrogen is useful as it coordinates with the metal M (Figure S5 in the SI) and the resulting M−N−C structure improves the local electronic structure leading to faster electrochemical process . The incorporation of N is also evidenced by the C 1s spectrum in the Figure b where a distinct peak at 285.2 eV is observed for C−N bonds . Moreover, C 1s also verifies the presence of C−C/C=C (284.5 eV), C=O (287.3 eV) and π‐π* (290.8 eV) bonds in FeCo@NC‐12 sample.…”
Section: Resultssupporting
confidence: 59%
“…It is already reported that the excessive pyridinic nitrogen is useful as it coordinates with the metal M (Figure S5 in the SI) and the resulting M−N−C structure improves the local electronic structure leading to faster electrochemical process . The incorporation of N is also evidenced by the C 1s spectrum in the Figure b where a distinct peak at 285.2 eV is observed for C−N bonds . Moreover, C 1s also verifies the presence of C−C/C=C (284.5 eV), C=O (287.3 eV) and π‐π* (290.8 eV) bonds in FeCo@NC‐12 sample.…”
Section: Resultssupporting
confidence: 59%
“…To improve the utilization rate of the atoms and expose more active sites, it is considered to improve the catalyst from two aspects. First, the catalytic properties of the material can be improved by regulating the structure of the material, such as ultra‐thinning of the material, regulating the size of the material, and design of multi‐level pore structures to expose more active sites . Xie et al.…”
Section: Introductionmentioning
confidence: 71%
“…The high-resolution Fe 2p spectrum of Fe/NS/C-g-C 3 N 4 /TPTZ-1000 presents two major peaks at around 711 and 724 eV, corresponding to Fe 2p 1/2 and Fe 2p 3/2 , respectively (Figure 6f) [15,35]. The dominant peak at 711 eV can be assigned to Fe 3+ or Fe 2+ coordinated with N, which are suggested to be the ORR active centers [15,36]. The peak at 718.5 eV is a satellite peak indicating the co-existence of Fe 3+ and Fe 2+ in the Fe/NS/C-g-C 3 N 4 /TPTZ-1000 [35].…”
Section: Resultsmentioning
confidence: 98%